Meningkatkan Kemampuan Moral dan Agama Anak Melalui Metode Demonstrasi di Taman Kanak-Kanak - Rinah, Rinah (ANTHOR: Education and Learning Journal, 2023)
The background of this research is that children are not yet able to be polite to fellow friends. Thepurpose of this study was to improve the moral and religious abilities of children through thedemonstration method at Mutiara Bunda Kindergarten in Palung Raya for the 2022 academic year. This research was conducted on Wednesday mornings from 07.35 to 11.00 on October 12 2022. This research included classroom action research (PTK) carried out in 2 cycles, which consists of planning, implementing, observing, and reflecting on the body. As the subject of this study were the children of Mutiara Bunda Kindergarten, Tambang District, Kampar Regency. Data collection techniques used observation and assignments in core activities, in order to obtain information about the activeness of children in participating in the teaching and learning process. The results of research on children's morals and religion through the demonstration method at Mutiara Bunda Kindergarten, Tambang District, Kampar Regency, can be improved using the demonstration method. Improving moral and religious abilities using the demonstration method in cycle I and cycle II developed very well. This is illustrated by the results of observations on moral and religious abilities in children. The first cycle of research and discussion results obtained children who were able to develop well and easily understand the material given by 55% and the second cycle developed very well and experienced an increase in morals and religion through demonstration methods, and cards or equal to 77%.